2015
DOI: 10.1093/iwc/iwv023
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Three Electroencephalogram Headsets for Brain–Computer Interfaces: A Within Subject Comparison

Abstract: Currently the field of brain-computer interfacing is increasingly focused on developing usable brain-computer interfaces (BCIs) to better ensure technology transfer and acceptance. Many studies have investigated the usability of BCI applications as a whole. Here we aim to investigate one specific component of an electroencephalogram (EEG)-based BCI system: the acquisition component. This study compares on the usability of three different EEG headsets in the context of a P300-based BCI application for communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 39 publications
(69 reference statements)
5
33
0
3
Order By: Relevance
“…It will produce a slight offset, hence a slight inaccuracy. Another alternative is to make separate measures by repeating the recordings with each system (Nijboer et al, 2015), but once again the conditions could not be exactly the same.…”
Section: Introductionmentioning
confidence: 99%
“…It will produce a slight offset, hence a slight inaccuracy. Another alternative is to make separate measures by repeating the recordings with each system (Nijboer et al, 2015), but once again the conditions could not be exactly the same.…”
Section: Introductionmentioning
confidence: 99%
“…Nijboer et al [31] reported that a 32-channel Biosemi system produced higher P300-based BCI accuracy than an 8-channel g.Sahara or 14-channel EPOC systems; however, the BioSemi system and the g.Sahara system were comparable when their performances using the same eight electrode sites were compared. Hariston et al [32] compared the EPOC, QUASAR, and B-Alert X-10 (Advanced Brain Monitoring) systems with the BioSemi system, which they considered the gold standard.…”
Section: Recording Methodsmentioning
confidence: 99%
“…Too much pressure may be uncomfortable for the user, whereas insufficient pressure affects the quality of the recording. Users have found that the jell used with typical wet electrodes is unpleasant, but dry electrodes may not yet produce comparable results . BCI performance would be improved by a better signal‐to‐noise ratio than that produced by current sensor technology.…”
Section: Some Characteristics Of Bcismentioning
confidence: 99%